2014
DOI: 10.1097/dcc.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Manager Residency Program

Abstract: To ensure succession planning within the ranks of nurse managers meet current and projected nursing management needs and organizational goals, we developed and implemented a nurse manager residency program at our hospital. By identifying, supporting, and mentoring clinical experts who express a desire and display an aptitude for nursing leadership, we are graduating individuals who can transition to a nurse manager position with greater ease and competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…10 This program spans a year and provides opportunities to participate in the organization's leadership development series, as well as a quarterly educational series led by the CNO, and completion of an evidencebased practice project. 10 The residency program is an effective way to begin preparing candidates and validating competencies before they accept a formal management position. 10…”
Section: Successful Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 This program spans a year and provides opportunities to participate in the organization's leadership development series, as well as a quarterly educational series led by the CNO, and completion of an evidencebased practice project. 10 The residency program is an effective way to begin preparing candidates and validating competencies before they accept a formal management position. 10…”
Section: Successful Strategiesmentioning
confidence: 99%
“…10 The residency program is an effective way to begin preparing candidates and validating competencies before they accept a formal management position. 10…”
Section: Successful Strategiesmentioning
confidence: 99%
“…Several descriptive, exploratory nursing studies have been conducted on nurse manager training. [20][21][22][23] Computer-based education provides an effective and costefficient approach to educating and engaging large numbers of leaders within a healthcare organization. Educational interventions have been found to be effective in improving leadership skills competency.…”
Section: Introductionmentioning
confidence: 99%
“…Several descriptive, exploratory nursing studies have been conducted on nurse manager training 20-23. However, no studies were identified that examined the effects of training and strength-based coaching on nurse managers' perceptions of leadership style and skills, as well as patient and staff outcomes over time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is important to highlight that the processes of characterization of professional profiles can begin even before the stage of hiring the workers, that is, during the selection and recruitment process carried out by the institution, since this movement also assists in the adequate allocation of workers, so that they effectively correspond to the position established. In this case, the personnel manager must establish a plan for the recruitment and permanent education processes, since misleading hiring has a negative impact on the performance of each function, directly reflecting on job satisfaction, on the professional engagement, as well as on the evaluation of results for the users and financial resources 5-6 .…”
Section: Introductionmentioning
confidence: 99%